Genetically modified herbicide tolerant crops – Aims and apprehensions - Naidu, V S G R; Varshney, Jay G (Indian Farming, 2015)
High adaptation rates of GMHT crops reflect farmers satisfaction with the products that offer substantial benefits ranging from more convenient and flexible crop management, lower cost of production, higher productivity or net returns per hectare, health and social benefits and a cleaner environment through decreased use of conventional pesticides, which collectively contribute to a more sustainable agriculture. However, herbicidetolerant crops are a relatively new and powerful tool in the integrated weed management (IWM) toolbox, but they must be used in a mutually supportive fashion with other weed management practices. The HT crops are essential components of the IWM system, but their value can be preserved only by proper management and reduced over use. This becomes even more important when other HT crops become more readily available (e.g. Roundup-Ready corn). Therefore, proper use of HT technology, as a component of IWM programme, is the key to preserving the long-term benefits of this technology while avoiding many of the concerns about their use or misuse (e.g. overuse). To preserve the effectiveness of glyphosate as long as possible, several resistance management strategies have been proposed by weed specialists such as rotating crops and using a variety of different herbicides to control weeds, practices that hinder resistant organisms from gaining a foothold in the growers’ fields. In practice, this means rotating crops that do not rely on using glyphosate. Another strategy is to use GM crops resistant to other herbicides, such as glufosinate. If so, this will allow growers to rotate their crops between varieties resistant to at least two different herbicides, giving farmers an alternative to the continual use of Glyphosate Resiatant Crops (GRCs), which would considerably delay the appearance of weeds resistant to glyphosate. Another approach is to combine, or ‘stack’, genes for resistance to multiple herbicides in the same plant. One question that arises is whether crops resistant to multiple herbicides will prolong the useful life of glyphosate. Another question is whether all the approaches described above to preserve the effectiveness of glyphosate will be followed by growers in developing countries, where the protocols of resistance management are usually less rigid than in developed countries. Therefore, HTC should be used in accordance with the principles of IWM.